Integrin alpha 2 beta 1 is upregulated in fibroblasts and highly aggressive melanoma cells in three-dimensional collagen lattices and mediates the reorganization of collagen I fibrils (The Rockefeller University Press, 1991)
The ability of cultured human fibroblasts to reorganize and contract three dimensional collagen I gels is regarded as an in vitro model for the reorganization of connective tissue during wound healing. We investigated whether adhesion receptors of the integrin family are involved. It was found that synthesis and transcription of the alpha 2 beta 1 integrin (but not of alpha 1 beta 1 or alpha 3 beta 1) is selectively upregulated when fibroblasts are seeded into type I collagen gels. Time course experiments revealed that high synthetic levels of alpha 2 beta 1 parallel the gel contraction process and return to "baseline" levels after the contraction has subsided. Furthermore, function-blocking mAbs directed to the alpha 2 and beta 1 chain of integrins inhibited gel contraction. Remodelling of connective tissue can be important for tumor cells during invasion and formation of metastases. Therefore, we tested human melanoma cell lines for this function. Five out of nine melanoma lines contracted collagen gels in vitro. Among these, two highly aggressive melanoma cell lines (MV3 and BLM) most efficiently contracted gels almost reaching the rate of normal adult fibroblasts. In these cells, synthesis of alpha 2 beta 1 was also significantly upregulated when seeded into collagen I gels. Moreover, function blocking anti-alpha 2 in conjunction with anti-beta 1 chain mAbs completely inhibited gel contraction for several days. Other melanoma cells (530) with lower metastatic potential which were not able to contract gels, showed no induction of alpha 2 beta 1 synthesis in gel culture. Our results suggest an important role of integrin alpha 2 beta 1 in the contraction of collagen I by normal diploid fibroblasts during wound healing and in the reorganization of collagen matrices by highly aggressive human melanoma cells.